Total and Metabolically Active Microbial Community of Aerobic Granular Sludge Systems Operated in Sequential Batch Reactors: Effect of Pharmaceutical Compounds - Barbara Muñoz-Palazon; Aurora Rosa-Masegosa; Miguel Hurtado-Martinez; Alejandro Rodriguez-Sanchez; Alexander Link; Ramiro Vilchez-Vargas; Alejandro Gonzalez-Martinez; Jesus Gonzalez Lopez (Toxics, 2021)
Two aerobic granular sludge (AGS) sequential batch reactors were operated at a mild (15 °C) temperature for 180 days. One of those bioreactors was exposed to a mixture of diclofenac, naproxen, trimethoprim, and carbamazepine. The AGS system, operating under pressure from emerging contaminants, showed a decrease in COD, BOD5, and TN removal capacity, mainly observed during the first 100 days, in comparison with the removal ratios detected in the control bioreactor. After an acclimatisation period, the removal reached high-quality effluent for COD and TN, close to 95% and 90%, respectively. In the steady-state period, trimethoprim and diclofenac were successfully removed with values around 50%, while carbamazepine and naproxen were more recalcitrant. The dominant bacterial OTUs were affected by the presence of a mixture of pharmaceutical compounds, under which the dominant phylotypes changed to OTUs classified among the Pseudomonas, Gemmobacter, and Comamonadaceae. The RT-qPCR and qPCR results showed the deep effects of pharmaceutical compounds on the number of copies of target genes. Statistical analyses allowed for linking the total and active microbial communities with the physico-chemical performance, describing the effects of pharmaceutical compounds in pollution degradation, as well as the successful adaptation of the system to treat wastewater in the presence of toxic compounds.